TLR4 signalling in ischemia/reperfusion injury: a promising target for linking inflammation, oxidative stress and programmed cell death to improve organ transplantation outcomes - Wang, Sutian; Zhang, Kunli; Huang, Qiuyan; Meng, Fanming; Deng, Shoulong (Frontiers in Immunology, 2024)
Transplantations represent the principal therapeutic interventions for terminal organ failure, a procedure that has salvaged myriad lives annually. Ischemia/reperfusion injury (IRI) is frequently correlated with an unfavourable prognosis and is relevant for early graft dysfunction and graft survival. IRI constitutes a complex pathological state influenced by a series of factors such as oxidative stress, metabolic stress, leukocytic infiltration, programmed cell death pathways, and inflammatory immune responses. Reducing ischemia/reperfusion injury is one of the main directions of transplantation research. Toll-like receptors (TLRs) are important pattern-recognition receptors expressed on various organs that orchestrate the immune responses upon recognising PAMPs and DAMPs. Targeting the TLR4 signalling has recently been suggested as a promising approach for alleviating IRI by affecting inflammation, oxidative stress and programmed cell death (PCD). In this minireview, we summarise the role of TLR4 signalling in regulating inflammation, oxidative stress and PCD in organ transplantation and discuss their interactions during IRI. A detailed understanding of the multiple functions of TLR4 in IRI provides novel insights into developing therapies to improve organ transplantation outcomes.